Key Terms in Semiotics. - Martin, Bronwen (Key Terms., 2006)
What is semiotics? This term is applied in a wide range of disciplines from literary theory and film to law, architecture and communication studies. But what does it actually mean and how can we use it? Key Terms in Semiotics provides exactly the information that a student needs when encountering semiotics for the first time or as a more advanced reader wishing to do in-depth readings.